2013
DOI: 10.3329/bjpt.v20i2.17404
|View full text |Cite
|
Sign up to set email alerts
|

Plant taxonomic research in Bangladesh (1972-2012): A critical review

Abstract: Amid serious concerns over declining taxonomic research world-wide, Bangladesh showed positive trends over . Some important developments in the global arena over the last decade give a mixed view on the growth of taxonomic research. This demands revisiting Bangladesh's plant taxonomic research to identify major factors guiding its courses. Taxonomic papers published in three Bangladeshi journals and the Flora of Bangladesh (1972Bangladesh ( -2012 were analyzed using a scoring system. The present study reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The increased number of people involved in describing species indicated increased taxonomic effort. Other studies have similarly reported the increasing trend in taxonomic effort (e.g., Costello, Wilson & Houlding, 2012 ; Costello, May & Stork, 2013 ; Costello, Houlding & Wilson, 2014 ; Costello et al, 2015 ; Essl et al, 2013 ; Irfanullah, 2013 ) which must have contributed to the sustained high number of species described ( Appeltans et al, 2012 ). We found no change in skewness (of papers per author per year) over the past century, and that the percentage of “oncers” had not shown any trend in the past century and the largest proportion of “oncers” was only 35%.…”
Section: Discussionmentioning
confidence: 86%
“…The increased number of people involved in describing species indicated increased taxonomic effort. Other studies have similarly reported the increasing trend in taxonomic effort (e.g., Costello, Wilson & Houlding, 2012 ; Costello, May & Stork, 2013 ; Costello, Houlding & Wilson, 2014 ; Costello et al, 2015 ; Essl et al, 2013 ; Irfanullah, 2013 ) which must have contributed to the sustained high number of species described ( Appeltans et al, 2012 ). We found no change in skewness (of papers per author per year) over the past century, and that the percentage of “oncers” had not shown any trend in the past century and the largest proportion of “oncers” was only 35%.…”
Section: Discussionmentioning
confidence: 86%
“…Such rates of discovery need to note that the number of people involved in naming species, an indicator of taxonomic effort, has increased 3-6 times since the 1950's and continues to increase (Alroy, 2002;Essl et al, 2013;Irfanullah, 2013;Costello et al, 2012Costello et al, , 2013cCostello et al, , 2014aCostello et al, ,b, 2015. This is not because of more part-time taxonomists; the proportion of part-time authors has been relatively constant over time; i.e.…”
Section: Undiscovered Speciesmentioning
confidence: 93%